PERMAINAN EDUKASI ILMU FIQIHIBADAH WUDHU DAN SALAT BERBASIS ANDROID - anam, k; Fajrin, Alfannisa Annurrullah (Computer Science and Industrial Engineering, 2020)
Learning is a human activity that has been carried out from birth to the world until closing age. One of them is studying the science of ablution and prayer, prayer is an obligation of every Muslim who will be accounted for in the hereafter. Valid among them is determined by ablution. In the world of education is very influential on the world of children in terms of knowledge and behavior, learning that is fun and makes children want to know more is needed, in modern times with technological sophistication there is no limit in learning ablution and prayer wherever and whenever, especially in school, wrong only through the Android-based smartphone media in the form of game applications. Learning in schools using only the medium of books and blackboards makes students bored quickly, bored and limited time. The purpose of this research is to make an Android-based game application that contains ablution and prayer material displayed attractively and interactively as well as userfriendly as an additional medium for learning ablution and prayer at Madrasah level schools to further attract students' learning interest. Game applications are made with Unity software with C Sharp programming language.